Volume 7A: Fluids Engineering Systems and Technologies 2013
DOI: 10.1115/imece2013-62391
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Influence of the Suction Arrangement on the Performance of Twin Screw Compressors

Abstract: Screw compressors are complex flow systems, but operate upon simple considerations: they are positive displacement machines consisting of meshing rotors contained in a casing to form a working chamber, whose volume depends only on the angle of rotation. Their performance is highly affected by leakages, which is dependent on various clearances and the pressure differences across these clearances. Nowadays, the manufacturing and profiling techniques have matured so much, that rotors of even the most complex shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…2 A clear understanding of the flow processes is essential as it would greatly help the machine performance and, in fact, their characteristics should be an integrated part of the design and optimisation process of screw compressors. 3,[11][12][13] The flow within the screw compressor can be divided into four sections, from suction to the exhaust. The first is the suction flow that feeds into the second section of five rotors' working chambers through which the gas is pressurised as it is convicted towards the third section of discharge port, where the flow exits into the last section of the discharge cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A clear understanding of the flow processes is essential as it would greatly help the machine performance and, in fact, their characteristics should be an integrated part of the design and optimisation process of screw compressors. 3,[11][12][13] The flow within the screw compressor can be divided into four sections, from suction to the exhaust. The first is the suction flow that feeds into the second section of five rotors' working chambers through which the gas is pressurised as it is convicted towards the third section of discharge port, where the flow exits into the last section of the discharge cavity.…”
Section: Introductionmentioning
confidence: 99%
“…13 The simulation by12 has shown that the suction port shape and the inflow trajectory into the rotors’ chambers would influence the flow within the rotors. The investigations of Stosic 2 and Pascu et al 12 have shown that the use of new techniques for rotors profiling helped to manufacture rotors of complex shapes with tolerances of the order of few microns, which improved efficiencies. Also, a limited number of the previous investigations have been carried out 19,20 to characterise flow leakages using experiments and CFD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common approaches, 0D chamber-model simulations, is described in the work by Kauder [5]. For a systematic introduction to 3D CFD simulations we refer to Kovacevic et al [6], while advanced CFD simulations including leakage flows are presented in [7,8]. A novel efficient tool for fluid domain meshing is proposed by Hesse [9].…”
Section: Introductionmentioning
confidence: 99%